2010
DOI: 10.1111/j.1570-7458.2010.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

A protein‐based approach to mark arthropods for mark‐capture type research

Abstract: A series of studies was conducted to test methods for marking a wide variety of arthropods with inexpensive proteins for mark-capture dispersal research. The markers tested included egg albumin protein in chicken egg whites and casein protein in bovine milk. The first study qualified the effectiveness of the two marks on more than 50 arthropod species inhabiting cotton via two application procedures. The application methods included: (1) a topical plus residue protein application, and (2) a residue-only protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 40 publications
4
52
1
3
Order By: Relevance
“…Because the cuticle is shed during molting, nymphs lose the marker between instars. However, because individuals can reacquire the marker from the plant (Hagler and Jones 2010), and plants were sprayed at 30-d intervals, it is unlikely that molting had a signiÞcant contribution to the overall number of nonmarked individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the cuticle is shed during molting, nymphs lose the marker between instars. However, because individuals can reacquire the marker from the plant (Hagler and Jones 2010), and plants were sprayed at 30-d intervals, it is unlikely that molting had a signiÞcant contribution to the overall number of nonmarked individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A buffer zone of two rows between plots was used to avoid marker drift to adjacent plots. Although insects can acquire the protein markers via direct contact with sprays and residual contact by walking on the surface of a treated plant part, the goal was to mark as many individuals as possible topically as they were resting on the plant (Hagler and Jones 2010). To minimize insect disturbance, markers were applied during the early morning periods (5:30 Ð 8:30 a.m.) when H. vitripennis were less active.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous markÐre-leaseÐrecapture work with insects of medical and veterinary concern has almost exclusively used ßuores-cent powders (Reisen and Lothrop 1995, Walton et al 1999, La Corte Dos Santos et al 2004, Maciel-deFreitas et al 2007, Casanova et al 2009). However, the development of immunomarking procedures offers a potential new method for studies in medical and veterinary environments (Jones et al 2006, Hagler and Jones 2010, Jones et al 2011. These new markers are cost-effective, highly sensitive, well suited to markÐ capture studies, and improve information on the potential impact of insect pest dispersal (Cameron et al 2009).…”
mentioning
confidence: 99%
“…Specifically, they showed that different water sources, additives (surfactants), and even the type of ELISA plate used affected (either positively or negatively) the assay. Moreover, that study and subsequent studies 37,39,40 showed that the three protein mark detection assays vary in efficacy. The egg white marker was retained longer than the milk marker, which was retained longer than soy milk marker.…”
Section: Introductionmentioning
confidence: 99%